Composite retarder, long-initial-setting super-wear-resistant corundum plastic material and preparation method of long-initial-setting super-wear-resistant corundum plastic material

By using composite retarders and corundum powder, the initial settling time of phosphate combined with wear-resistant plastics is extended, and the problem of insufficient material strength and wear resistance is solved, and the effect of high strength and ultra-wear resistance is achieved, which is suitable for the refractory material needs of high-temperature industries.

CN119841652APending Publication Date: 2025-04-18PUYANG REFRACTORIES GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510001652.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing phosphate combined with wear-resistant plastics have a short time during the initial setting process, resulting in a decrease in material strength and wear resistance, which cannot meet the high requirements of high-temperature industry for wear resistance.

Method used

Compound retarder is used, consisting of polyamino acids, acryl polyethers and melamine-type sulfonated polycondenser, and uses this as an admixture, combining corundum powder, micro powder and other additives to extend the initial settling time and improve the strength and wear resistance of the material.

Benefits of technology

It realizes the ultra-long initial settling time of plastic, has high strength and strong wear resistance, and can be sintered at a high temperature of 800℃, meeting the needs of high wear resistance, and improving construction efficiency and overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841652A_ABST
    Figure CN119841652A_ABST
Patent Text Reader

Abstract

The invention relates to a composite retarder, a long-initial-setting super-wear-resistant corundum plastic refractory and a preparation method of the long-initial-setting super-wear-resistant corundum plastic refractory. The composite retarder is prepared from polyamino acid, allyl alcohol polyether and melamine type sulfonated polycondensate. The plastic refractory raw material consists of 45-65% of corundum aggregate, 15-30% of corundum powder, 10-20% of micro powder, 3-5% of plasticizer and 3-5% of coagulant; 0.1-0.5% of a plasticizer, 0.3-2% of a composite retarder, 0.05-0.2% of fibers, 3.5-5% of a ageing agent and 3.5-6% of a binding agent based on the total weight of the raw materials are added. According to the composite retarder, the reaction of a binding agent and a coagulant can be obviously delayed, the calorific value is reduced, the initial setting time reaches 1-2 h, sufficient construction time is provided, the obtained plastic refractory has the characteristics of high strength and super wear resistance, a plastic refractory lining has good anti-scouring and anti-wear effects in a high-temperature kiln, and safe and stable operation of the kiln is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high temperature wear-resistant materials, in particular to a composite retarder and a long initial setting super wear-resistant corundum plastic material and a preparation method thereof. Background Art

[0002] In the context of energy conservation and emission reduction, the development of super wear-resistant materials is of great significance for high-temperature industries to reduce refractory consumption and improve kiln operation rate and production efficiency. Corundum has a granular or plate-like crystal structure, small pores and more closed pores. Its main component is α-alumina, which has the characteristics of high temperature resistance, high strength, stable chemical properties, and acid and alkali resistance.

[0003] When traditional phosphate-bonded wear-resistant plastics are constructed at 25-35°C, liquid phosphates and coagulants react quickly and release heat, causing the material to initially set in 10-20 minutes and lose plasticity. The only way to solve the problem of rapid initial setting of the material is to reduce the coagulant, which will significantly reduce the strength and wear resistance of the material. This is a key problem restricting phosphate-bonded wear-resistant plastics, and the global refractory industry has not yet solved this problem well. In addition, with the large-scale development of circulating fluidized bed boilers and petrochemical equipment, the wear resistance requirements for refractory materials are getting higher and higher, and the wear resistance value is less than 5cm. 3 Traditional plastics cannot meet the use requirements under some conditions. Since the material is difficult to sinter at 800℃ and the strength is difficult to improve, the wear resistance value is less than 2.5cm. 3 There is an urgent need for super wear-resistant plastics. Summary of the invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to extend the initial setting time of plastic while ensuring the strength and wear resistance of the plastic, and further improve the strength and wear resistance of the material. Based on this, the present invention provides a composite retarder and a long initial setting super wear-resistant corundum plastic and a preparation method thereof, which has the characteristics of super long initial setting time, high strength and super wear resistance.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention provides a composite retarder, which consists of polyamino acid, acryl alcohol polyether and melamine type sulfonated polycondensate.

[0007] Preferably, the composite retarder is composed of 0.5 to 1.5 parts of polyamino acid, 0.5 to 1.5 parts of allyl alcohol polyether and 0.1 to 1.0 parts of melamine type sulfonated polycondensate, in parts by mass.

[0008] Preferably, the polyamino acid is poly(α-amino acid); the acryl alcohol polyether is propylene glycol polyoxypropylene polyoxyethylene ether; the melamine type sulfonated polycondensate is sulfonated melamine formaldehyde resin; and the pH of the composite retarder is 5-6.

[0009] Preferably, the preparation method of the composite retarder is: according to the construction environment temperature requirement, the components of the composite retarder are weighed according to the proportion, stirred in a mixer for 7 to 8 minutes, and then the composite retarder can be used.

[0010] The present invention provides a long initial setting super wear-resistant corundum plastic material, which is composed of raw materials and external components; the external components include the composite retarder;

[0011] In terms of weight percentage, the raw material of the long initial setting super wear-resistant corundum plastic material is composed of 45-65wt% of corundum aggregate, 15-30wt% of corundum powder, 10-20wt% of micro powder, 3-5wt% of plasticizer and 3-5wt% of coagulant, and the total weight of the above raw materials is 100%;

[0012] 0.1-0.5wt% of plasticizer, 0.3-2wt% of composite retarder, 0.05-0.2wt% of fiber, 3.5-5wt% of material trapping agent and 3.5-6wt% of binder are added to the total weight of the above raw materials.

[0013] Preferably, the corundum aggregate is any one or more combinations of plate-like corundum, brown corundum, white corundum, chrome corundum, and special-grade alumina; the corundum powder is any one or more combinations of plate-like corundum powder, brown corundum powder, white corundum powder, chrome corundum powder, and special-grade alumina powder; the micropowder is two or more combinations of alumina micropowder, plate-like corundum micropowder, white corundum micropowder, magnesia-alumina spinel micropowder, and white carbon black.

[0014] Preferably, the chemical composition of the corundum aggregate is Al2O3≥88wt%; the particle size range of the corundum powder is: 0.088~0.044mm; the chemical composition of the alumina micropowder, plate-like corundum micropowder and white corundum micropowder is Al2O3≥99wt%; the chemical composition of the magnesia-alumina spinel micropowder is Al2O3≥70wt%, MgO≤25wt%; the chemical composition of the white carbon black is SiO2≥95wt%; the D50 of the alumina micropowder, plate-like corundum micropowder, white corundum micropowder and magnesia-alumina spinel micropowder is: 1~4μm.

[0015] Preferably, in terms of particle size range, the corundum aggregate includes: particle size A of 1-3 mm, particle size B of 0.5-1 mm and particle size C of 0-0.5 mm; the mixing mass ratio of particle size A, particle size B and particle size C is (18-35): (10-15): (10-15).

[0016] In terms of mass fraction, the micropowder consists of 5-15 parts of alumina micropowder, 0-10 parts of plate-like corundum micropowder, 0-10 parts of white corundum micropowder, 0-8 parts of magnesia-aluminum spinel micropowder and 1-3 parts of white carbon black.

[0017] The present invention uses several raw materials to form a composite micro powder, which can fill the gaps of different pore sizes and make the material dense. White carbon black has a deep submicron particle size, which further fills the pores of other powders and makes the material densest.

[0018] Preferably, the mixing mass ratio of corundum aggregate, corundum powder and micro powder is (45-65): (15-30): (10-20);

[0019] Preferably, the coagulant is pure aluminate cement or magnesia; the chemical composition of the pure aluminate cement contains CaO < 30wt%, Al2O3 > 70wt%; the chemical composition of the magnesia contains MgO > 97wt%, CaO < 1.5wt%; the plasticizer is bentonite or Guangxi white mud; the chemical composition of the plasticizer contains Al2O3 > 30wt%; and the D50 of the plasticizer is < 0.5μm.

[0020] Preferably, the plasticizer is carboxymethyl cellulose and hydroxypropyl methyl cellulose, which are solid powders;

[0021] The fiber is a combination of two or more of an organic fiber with a melting point of 160°C, an organic fiber with a melting point of 105°C, and an organic fiber with a melting point of 60-70°C; the length of the fiber is 3-5 mm; the trapping agent is phosphoric acid liquid; the concentration of the phosphoric acid liquid is 30-50 wt%; the binder is aluminum dihydrogen phosphate liquid; the specific gravity of the aluminum dihydrogen phosphate liquid is 1.30-1.45 g / cm 3 .

[0022] Among them, the plasticizer forms a colloid after dissolving in the liquid, which can increase the viscosity of the slurry and prevent the components from separating and settling; the fiber in the plastic can improve the construction flexibility of the plastic. And the fiber components have different melting points. During the baking process, the vapor pressure can be released in stages, effectively improving the lining's anti-burst ability.

[0023] The present invention uses liquid phosphoric acid. On the one hand, the phosphoric acid trapping material is used to remove iron oxide impurities and prevent the iron oxide in the material from reacting with the liquid aluminum dihydrogen phosphate to generate hydrogen and expand. On the other hand, the aluminum dihydrogen phosphate can be reduced to improve the strength.

[0024] The preparation method of the aluminum dihydrogen phosphate liquid is as follows: liquid phosphoric acid, solid aluminum hydroxide powder, oxalic acid and water are mixed and reacted in a high-temperature container according to the raw material ratio to obtain a liquid with a specific gravity of 1.30 to 1.45 g / cm 3The aluminum dihydrogen phosphate solution is white and transparent with stable solubility.

[0025] Preferably, the mass ratio of the carboxymethyl cellulose to the hydroxypropyl methyl cellulose is 1:1 or 2:1;

[0026] In terms of weight fraction, the fiber consists of 0.02-0.1 parts of organic fiber with a melting point of 160°C, 0.02-0.1 parts of organic fiber with a melting point of 105°C and 0-0.1 parts of organic fiber with a melting point of 60-70°C.

[0027] The present invention provides a method for preparing the long initial setting super wear-resistant corundum plastic material, comprising the following steps:

[0028] (1) Weigh each component according to the composition of raw materials and added components and set aside;

[0029] (2) First, corundum aggregate, corundum powder, micro powder, plasticizer, plasticizer, composite retarder and fiber are mixed evenly, put into a mixer, and a binding agent is added, and stirred for T1 to form a semi-humid state (this step can not only consume the residual iron oxide in the material and prevent the sample from expanding, but more importantly, it can reduce the amount of subsequent liquid aluminum dihydrogen phosphate added, which is beneficial to improving the sintering strength); then, a coagulant is added, and stirred for T2, and finally, a binder is added, and stirred for T3 to form a soft dough;

[0030] (3) pressing the mixed material prepared in step (2) into a mold, pounding it into shape, and finally smoothing the surface; demoulding it after curing, and drying it;

[0031] (4) The dried sample is placed in a high-temperature kiln for firing, and after cooling, the product is obtained.

[0032] Preferably, in the step (2), the stirring time T1 is 3-5 min; the stirring time T2 is 1-3 min; the stirring time T3 is 3-5 min; in the step (3), the curing time is 24-48 h; the drying temperature is 110-120° C., and the drying time is 22-26 h; in the step (4), the sintering temperature is 800-1100° C., and the insulation time is 180 min.

[0033] Preferably, under the condition of 25-35°C, without reducing the accelerator, the initial setting time of the long initial setting super wear-resistant corundum plastic is 1-2h, and the bulk density after burning at 800°C is ≥2.85g / cm 3 , flexural strength ≥ 28MPa, compressive strength ≥ 170MPa, wear resistance value < 2.5cm 3 , line change rate 0~-0.2%.

[0034] The technical solution of the present invention achieves the following beneficial technical effects:

[0035] The present invention uses polyamino acid, acryl polyether and melamine sulfonated polycondensate to prepare a composite retarder, and uses the composite retarder as an admixture. The raw material is mainly corundum powder, and a composite ratio of various corundum fine powders and micropowders is used, and plasticizers and accelerators are added. Composite fibers, plasticizers, trapping agents and binders with different melting points are added to prepare a long initial setting and super wear-resistant corundum plastic. The plastic of the present invention has an initial setting time of 1 to 2 hours without reducing the accelerator, and the obtained plastic has the characteristics of high strength and super wear resistance. The present invention provides sufficient construction time, which can fully guarantee the construction quality, so that the plastic lining can play a good anti-scouring and anti-wear effect in the high-temperature kiln, and ensure the safe and stable operation of the kiln. The specific analysis is as follows:

[0036] The composite retarder of the present invention has strong activity on the surface of the hydration product of the accelerator (cement or magnesia particles), can produce adsorption at the solid-liquid interface, form a layer of insoluble film, play a barrier role in the hydration of cement or magnesia particles, form unstable complexes with calcium and magnesium ions, control the concentration of calcium and magnesium ions in the liquid phase at the initial stage of hydration, change the structural morphology, hinder normal hydration, and produce a retarding effect. Due to the adsorption effect on the gel, the speed of crystal embryo generation in the saturated solution is changed, thereby controlling the hydration and hardening process of the gel. As time goes by, the expansion of cement or magnesia particles causes the gaps between the adsorption layer molecules to expand or the film layer to rupture, and the unstable complex will be destroyed, so the hydration can proceed as usual and will not affect the strength. Under the condition of 25-35°C without reducing the accelerator, the initial setting time is 1-2h, and it has ultra-high wear resistance, which can reduce the consumption of refractory materials and ensure the safe and stable operation of the kiln.

[0037] Currently, conventional phosphate plastics do not have any retarders, and the initial setting time can only be extended by reducing the accelerator. The composite retarder of the present invention can significantly delay the reaction of the binder (liquid aluminum dihydrogen phosphate) and the accelerator, reduce the heat generation, and make the initial setting time reach 1 to 2 hours, which is unattainable by conventional plastics. Compared with the existing traditional wear-resistant plastics, the present invention does not need to reduce the accelerator, has an ultra-long initial setting time, high construction efficiency, and good construction quality. The plastic of the present invention has ultra-high bonding strength, flexural strength ≥28MPa after burning at 800°C, compressive strength ≥170MPa, and wear resistance value <2.5cm 3 When using the plastic lining of the present invention, during the baking stage, before the critical point of water volatilization, a steam exhaust channel can be formed inside the material, effectively reducing the destructive effect of steam pressure on the lining, and meeting the requirements of fast and safe baking. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A physical picture of the long initial setting super-wear-resistant corundum plastic obtained in Example 1 of the present invention after wear resistance testing. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and technical effect of the invention of this application clearer, the technical scheme in the embodiment of this application will be clearly and completely described below in conjunction with the drawings in the embodiment of this application. Obviously, the described embodiment is a part of the embodiment of this application, not all the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0040] The long initial setting super wear-resistant corundum plastic material and the preparation method thereof are described in detail below through specific embodiments.

[0041] The raw materials used in the embodiment of the present invention are: Al2O3≥88wt% in the chemical composition of corundum aggregate; Al2O3≥99wt% in the chemical composition of alumina micropowder, plate-shaped corundum micropowder, and white corundum micropowder; Al2O3≥70wt% and MgO≤25wt% in the chemical composition of magnesium aluminum spinel micropowder; SiO2≥95wt% in the chemical composition of white carbon black; CaO<30wt% and Al2O3>70wt% in the chemical composition of pure aluminate cement; MgO>97wt% and CaO<1.5wt% in the chemical composition of high-purity magnesia; Al2O3>30wt% in the chemical composition of plasticizer; and D50 of plasticizer<0.5μm. The length of the fiber is 3-5mm.

[0042] The preparation method of the composite retarder is as follows: weigh 1.0 parts by mass of polyamino acid (poly-α-amino acid), 0.5 parts by mass of propylene alcohol polyether (propylene glycol polyoxypropylene polyoxyethylene ether) and 0.5 parts by mass of melamine type sulfonated condensation product (sulfonated melamine formaldehyde resin), stir in a mixer for 7 to 8 minutes, and the pH of the obtained composite retarder is 5.2.

[0043] The preparation method of aluminum dihydrogen phosphate liquid is as follows: liquid phosphoric acid, solid aluminum hydroxide powder, oxalic acid and water are mixed in a high temperature container according to the raw material ratio to react, and the specific gravity is 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 of aluminum dihydrogen phosphate liquid.

[0044] Example 1

[0045] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 63wt% of corundum aggregate, 19wt% of corundum powder, 12wt% of micro powder, 3wt% of plasticizer, and 3wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0046] 0.3wt% of plasticizer, 0.3wt% of composite retarder, 0.05wt% of fiber, 3.5wt% of material trapping agent and 4wt% of binder were added to the total weight of the above raw materials.

[0047] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 1.

[0048] Table 1

[0049]

[0050] The method for preparing the long initial setting super wear-resistant corundum plastic comprises the following steps:

[0051] (1) Weigh each component according to the composition of raw materials and added components and set aside;

[0052] (2) First, mix the corundum aggregate, corundum powder, micro powder, plasticizer, plasticizer, composite retarder and fiber evenly, put them into a mixer, add the binding agent, stir for 3 minutes, and turn them into a semi-wet state; then add the accelerator, stir for 1 minute, and finally add the binder, stir for 3 minutes, and turn them into a soft dough;

[0053] (3) Pressing the mixed material prepared in step (2) into a mold, pounding it into shape, and finally smoothing the surface; after curing for 24 hours, demoulding, and drying at 110° C. for 24 hours;

[0054] (4) Place the dried sample into a high-temperature kiln, sinter it at 800°C, keep it warm for 180 minutes, and cool it down to obtain the final product.

[0055] Example 2

[0056] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 58wt% of corundum aggregate, 19.5wt% of corundum powder, 15.5wt% of micro powder, 4wt% of plasticizer, and 3wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0057] 0.2 wt% of plasticizer, 0.8 wt% of composite retarder, 0.1 wt% of fiber, 3 wt% of material trapping agent and 4.5 wt% of binder were added to the total weight of the above raw materials.

[0058] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 2.

[0059] Table 2

[0060]

[0061] The preparation method of the long initial setting super wear-resistant corundum plastic is the same as that of Example 1.

[0062] Example 3

[0063] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 53wt% of corundum aggregate, 21wt% of corundum powder, 18wt% of micro powder, 5wt% of plasticizer, and 3wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0064] 0.1 wt% of plasticizer, 1.2 wt% of composite retarder, 0.15 wt% of fiber, 3.5 wt% of material trapping agent and 4.5 wt% of binder were added to the total weight of the above raw materials.

[0065] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 3.

[0066] Table 3

[0067]

[0068] The preparation method of the long initial setting super wear-resistant corundum plastic is the same as that of Example 1.

[0069] Example 4

[0070] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 53wt% of corundum aggregate, 23wt% of corundum powder, 18wt% of micro powder, 3wt% of plasticizer, and 3wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0071] 0.3 wt% of plasticizer, 1.6 wt% of composite retarder, 0.15 wt% of fiber, 3.5 wt% of material trapping agent and 4.5 wt% of binder were added to the total weight of the above raw materials.

[0072] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 4.

[0073] Table 4

[0074]

[0075] The preparation method of the long initial setting super wear-resistant corundum plastic is the same as that of Example 1.

[0076] Example 5

[0077] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 58wt% of corundum aggregate, 18.5wt% of corundum powder, 15.5wt% of micro powder, 4wt% of plasticizer, and 4wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0078] 0.2 wt% of plasticizer, 1.6 wt% of composite retarder, 0.15 wt% of fiber, 3.5 wt% of material trapping agent and 4.5 wt% of binder were added to the total weight of the above raw materials.

[0079] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 5.

[0080] Table 5

[0081]

[0082]

[0083] The preparation method of the long initial setting super wear-resistant corundum plastic is the same as that of Example 1.

[0084] Example 6

[0085] The present embodiment relates to a long initial setting super wear-resistant corundum plastic material, which comprises, by weight percentage, 47wt% of corundum aggregate, 27wt% of corundum powder, 18wt% of micro powder, 3wt% of plasticizer, and 5wt% of accelerator, wherein the total weight of the above raw materials is 100%;

[0086] 0.2 wt% of plasticizer, 1.6 wt% of composite retarder, 0.10 wt% of fiber, 4 wt% of material trapping agent and 5 wt% of binder were added to the total weight of the above raw materials.

[0087] The specific raw material composition of the long initial setting super wear-resistant corundum plastic material in this embodiment is shown in Table 6.

[0088] Table 6

[0089]

[0090] The preparation method of the long initial setting super wear-resistant corundum plastic is the same as that of Example 1.

[0091] Comparative Example 1

[0092] This comparative example involves a corundum plastic material. The difference between this comparative example and Example 1 is that this comparative example does not involve a composite retarder, and the composition, dosage and preparation method of other raw materials and additional components are the same as those of Example 1. The specific raw material composition of this comparative example is shown in Table 7.

[0093] Table 7

[0094]

[0095] Comparative Example 2

[0096] This comparative example involves a corundum plastic material. The difference between this comparative example and Example 1 is that this comparative example does not involve a composite retarder and a composite micropowder, and the composition, dosage and preparation method of other raw materials and additional components are the same as those of Example 1. The specific raw material composition of this comparative example is shown in Table 8.

[0097] Table 8

[0098]

[0099] Performance measurement and analysis:

[0100] According to the testing standard for amorphous refractory materials, the bulk density, flexural strength, compressive strength, wear resistance, linear change rate, and initial setting time at 35°C of the long initial setting super-wear-resistant corundum plastic (800°C×3h) obtained in the embodiment of the present invention were measured. The performance test results are shown in Table 9.

[0101] Among them, the photo of the long initial setting super wear-resistant corundum plastic obtained in Example 1 of the present invention after the wear resistance test is as follows Figure 1 shown.

[0102] Table 9

[0103]

[0104] As shown in Table 9, by adjusting the ratio of different micropowders, the long initial setting super wear-resistant plastic has a flexural strength of ≥28MPa, a compressive strength of ≥170MPa, and a wear resistance of 1.9-2.5cm after burning at 800℃. 3 , with high strength and super wear resistance. And the use of composite retarder solves the problem that phosphate plastic cannot adjust the initial setting time. At an ambient temperature of 35°C, the initial setting time can reach 60 to 120 minutes.

[0105] Compared with Example 1, Comparative Example 1 does not use a composite retarder, and the initial setting time is only 15 minutes. Due to the short initial setting time, the plastic hardens quickly during the molding process, and the pores are not densely filled, resulting in a decrease in bulk density, which affects the strength and also significantly decreases. Compared with Example 1, Comparative Example 2 does not use a composite retarder and composite micropowder, and the initial setting time is only 20 minutes. Due to the short initial setting time, the plastic hardens quickly during the molding process, and there is no micropowder to fill the fine pores, the density of the material is further reduced, and the strength after firing is significantly reduced.

[0106] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A composite retarder, characterized in that: The composite retarder consists of polyamino acid, acryl alcohol polyether and melamine type sulfonated polycondensate.

2. The composite retarder according to claim 1, characterized in that Calculated by weight, the composite retarder consists of 0.5 to 1.5 parts of polyamino acid, 0.5 to 1.5 parts of allyl alcohol polyether and 0.1 to 1.0 parts of melamine type sulfonated polycondensate.

3. The composite retarder according to claim 2, characterized in that The polyamino acid is poly(α-amino acid); the acryl alcohol polyether is propylene glycol polyoxypropylene polyoxyethylene ether; the melamine type sulfonated polycondensate is sulfonated melamine formaldehyde resin; and the pH value of the composite retarder is 5-6.

4. A long initial setting super wear-resistant corundum plastic, characterized in that: The long initial setting super wear-resistant corundum plastic material is composed of raw materials and added components; the added components include the composite retarder as described in any one of claims 1 to 3; In terms of weight percentage, the raw materials of the long initial setting super-wear-resistant corundum plastic material are composed of 45-65wt% of corundum aggregate, 15-30wt% of corundum powder, 10-20wt% of micropowder, 3-5wt% of plasticizer and 3-5wt% of accelerator, and the total weight of the above raw materials is 100%; in addition, 0.1-0.5wt% of the total weight of the above raw materials is added, as is 0.3-2wt% of the composite retarder, 0.05-0.2wt% of the fiber, 3.5-5wt% of the material-binding agent and 3.5-6wt% of the binder.

5. The long initial setting super wear-resistant corundum plastic according to claim 4, characterized in that: The corundum aggregate is any one or more combinations of plate-shaped corundum, brown corundum, white corundum, chrome corundum, and special grade alumina; The corundum powder is any one or more combinations of plate-like corundum powder, brown corundum powder, white corundum powder, chrome corundum powder, and special-grade alumina powder; The micro powder is a combination of two or more of alumina micro powder, plate-shaped corundum micro powder, white corundum micro powder, magnesium aluminum spinel micro powder and white carbon black.

6. The long initial setting super wear-resistant corundum plastic according to claim 5, characterized in that: The chemical composition of the corundum aggregate is Al2O3≥88wt%; the particle size range of the corundum powder is: 0.088~0.044mm; The chemical composition of the alumina micropowder, plate-shaped corundum micropowder and white corundum micropowder is Al2O3≥99wt%; the chemical composition of the magnesium aluminum spinel micropowder is Al2O3≥70wt%, MgO≤25wt%; the chemical composition of the white carbon black is SiO2≥95wt%; The D50 of the alumina micropowder, plate-shaped corundum micropowder, white corundum micropowder, and magnesium aluminum spinel micropowder is 1 to 4 μm; In terms of particle size range, the corundum aggregate includes: particle size A of 1-3 mm, particle size B of 0.5-1 mm, and particle size C of 0-0.5 mm; the mixing mass ratio of particle size A, particle size B, and particle size C is (18-35): (10-15): (10-15); In terms of mass fraction, the micropowder consists of 5-15 parts of alumina micropowder, 0-10 parts of plate-like corundum micropowder, 0-10 parts of white corundum micropowder, 0-8 parts of magnesia-aluminum spinel micropowder and 1-3 parts of white carbon black.

7. The long initial setting super wear-resistant corundum plastic according to claim 4, characterized in that: The coagulant is pure aluminate cement or magnesia sand; the chemical composition of the pure aluminate cement is CaO < 30wt%, Al2O3 > 70wt%; the chemical composition of the magnesia sand is MgO > 97wt%, CaO < 1.5wt%; The plasticizer is bentonite or Guangxi white mud; in the chemical composition of the plasticizer, Al2O3>30wt%; the D50 of the plasticizer is <0.5μm; The plasticizers are carboxymethyl cellulose and hydroxypropyl methyl cellulose; The fiber is a combination of two or more of an organic fiber with a melting point of 160°C, an organic fiber with a melting point of 105°C, and an organic fiber with a melting point of 60-70°C; the length of the fiber is 3-5 mm; The trapping agent is phosphoric acid liquid; the concentration of the phosphoric acid liquid is 30-50wt%; The binder is aluminum dihydrogen phosphate liquid; the specific gravity of the aluminum dihydrogen phosphate liquid is 1.30-1.45 g / cm 3 .

8. The long initial setting super wear-resistant corundum plastic according to claim 7, characterized in that: The mass ratio of the carboxymethyl cellulose to the hydroxypropyl methyl cellulose is 1:1 or 2:1; In terms of weight fraction, the fiber consists of 0.02-0.1 parts of organic fiber with a melting point of 160°C, 0.02-0.1 parts of organic fiber with a melting point of 105°C and 0-0.1 parts of organic fiber with a melting point of 60-70°C.

9. A method for preparing a long initial setting super wear-resistant corundum plastic, characterized in that: The following steps are involved: (1) Weigh the raw materials and external components of the long initial setting super wear-resistant corundum plastic material according to any one of claims 4 to 8 and set aside; (2) First, mix the corundum aggregate, corundum powder, micro powder, plasticizer, plasticizer, composite retarder and fiber evenly, put them into a mixer, add the material trapping agent, and stir for T1; then add the coagulant, stir for T2, and finally add the binder, and stir for T3; (3) pressing the mixed material prepared in step (2) into a mold; demoulding after curing, and drying; (4) calcining the dried sample and cooling it to obtain; The preparation method of the composite retarder is as follows: weigh each component of the composite retarder according to any one of claims 1 to 3, and stir evenly to obtain the composite retarder.

10. The preparation method according to claim 9, characterized in that: In the step (2), the stirring time T1 is 3-5 min; the stirring time T2 is 1-3 min; the stirring time T3 is 3-5 min; In the step (3), the curing time is 24-48 hours; the drying temperature is 110-120° C., and the drying time is 22-26 hours; In the step (4), the sintering temperature is 800-1100° C. and the heat preservation time is 180 minutes.